Lignin nanometer bottle-based photo-thermal super-hydrophobic deicing coating composition, coating, preparation method and application
The imine bond crosslinking supramolecular polymer formed by the reaction of modified lignin nanobottles with specific silicones solves the problem of insufficient weather resistance and self-healing properties of superhydrophobic coatings, and achieves efficient deicing and long-lived green coating applications.
Patent Information
- Application Number
- CN202510400991.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2025-07-04
- Estimated Expiration
- 2045-04-01
AI Technical Summary
In actual applications, the existing superhydrophobic coatings have poor weather resistance and insufficient self-healing properties, which are difficult to meet the needs of long-term stability and deicing efficiency, and traditional materials have poor environmental protection.
The mature modified lignin nanoflask was used to react with aminopropyl-terminated polydimethylsiloxane and phenylade to form an imine bond cross-linked hydrophobic supramolecular polymer. Combined with cetyltrimethylsiloxane and methyltrimethoxysiloxane, and prepared a lignin nanoflask-based photothermal superhydrophobic deicing coating with self-healing properties.
It improves the hydrophobic properties, weather resistance and deicing ability of the coating, extends its service life, is green and environmentally friendly, does not rely on fluoride, and has excellent self-healing and mechanical stability.
Smart Images

Figure CN120248763A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of coating materials, and particularly relates to a lignin-based nanobottle-based photothermal superhydrophobic deicing coating composition, a coating, and a preparation method and application thereof. Background Art
[0002] Disclosing the information of this background art section is only intended to increase the understanding of the overall background of the present invention, and is not necessarily regarded as an admission or an implication in any form that this information constitutes the prior art already known to those of ordinary skill in the art.
[0003] In recent years, superhydrophobic materials have attracted much attention in the field of anti / de-icing due to their excellent anti-wetting ability and low ice adhesion performance. The superhydrophobic coating reduces the contact area of water droplets on the surface, delays the freezing of water droplets or reduces the adhesion of water droplets, thereby achieving the anti-icing effect. However, due to the poor weather resistance of the material in the actual complex environment (such as temperature changes, ultraviolet radiation, mechanical damage, etc.), the performance of most current superhydrophobic coatings decays rapidly, making it difficult to meet the long-term stability requirements in practical applications. Moreover, the environmental friendliness of existing superhydrophobic materials is poor, often relying on fluoride or chemically synthesized polymer coatings, and this production and use method conflicts with the current concept of green and sustainable development. Therefore, it is of great significance to develop superhydrophobic coatings with excellent weather resistance and environmental friendliness.
[0004] Lignin has a photothermal effect and can absorb light energy and convert it into heat energy under light irradiation. Therefore, in the prior art, lignin is used to prepare superhydrophobic coatings to assist in de-icing, and the synergistic effect of the photothermal function and the superhydrophobic anti-icing performance helps to achieve the dual goals of "active anti-icing" and "passive de-icing", reducing external energy consumption. For example, H,1H,2H,2H-perfluorooctyltrichlorosilane is used to modify lignin, and a lignin superhydrophobic coating is prepared by using silane-modified lignin, nano-silica, polydimethylsiloxane, epoxy resin, and a curing agent. This coating relies on fluoride to reduce the surface energy of lignin, improve the hydrophobic performance and anti-icing effect of the coating, and does not have self-healing properties. In the actual application process, fluorosilane-modified lignin (low surface energy substance) is easily decomposed under the stimulation of temperature, light, strong oxidants, etc., with poor weather resistance, and its surface structure is also easily damaged under physical actions such as mechanical friction or wear, thereby affecting the adhesion and wettability of the coating, resulting in a decrease or loss of the waterproof and de-icing performance.
[0005] In summary, it is of great significance to develop a highly weather-resistant lignin-based superhydrophobic de-icing coating with self-healing properties. Summary of the Invention
[0006] In order to solve the shortcomings of the prior art, the purpose of the present invention is to provide a lignin nanobottle-based photothermal superhydrophobic deicing coating composition, coating and its preparation method and application. The lignin nanobottle-based photothermal superhydrophobic deicing coating provided by the present invention has excellent self-repairing performance, weather resistance and deicing performance, which solves the problems of poor weather resistance and low deicing efficiency of lignin-based superhydrophobic coatings in the prior art.
[0007] In order to achieve the above object, the technical solution of the present invention is:
[0008] The first aspect of the present invention provides a lignin nanobottle-based photothermal superhydrophobic deicing coating composition, which comprises, by weight: 1-20 parts of matured modified lignin nanobottle, 1-10 parts of aminopropyl-terminated polydimethylsiloxane, 1-10 parts of trimesicaldehyde, 10-100 parts of hexadecyl trimethylsiloxane, 10-70 parts of methyl trimethoxysiloxane, and 3000-3500 parts of solvent.
[0009] In some embodiments of the present invention, the ripened modified lignin nanobottle is obtained by heating and ripening the lignin nanobottle.
[0010] Preferably, the lignin nanobottle solution is aged at 80-200° C. for 2-20 hours and then dried to obtain the aged modified lignin nanobottle.
[0011] In some embodiments of the present invention, the solvent includes at least one of tetrahydrofuran, ethanol and acetone.
[0012] In some embodiments of the present invention, the lignin nanobottle-based photothermal superhydrophobic deicing coating composition includes, by weight: 5-15 parts of matured modified lignin nanobottle, 2-8 parts of aminopropyl-terminated polydimethylsiloxane, 2-8 parts of trimesic acid, 30-100 parts of hexadecyl trimethylsiloxane, 30-70 parts of methyl trimethoxysiloxane, and 3300-3400 parts of solvent.
[0013] In some embodiments of the present invention, the lignin nanobottle-based photothermal superhydrophobic deicing coating composition includes, by weight: 10-15 parts of matured modified lignin nanobottle, 5-8 parts of aminopropyl-terminated polydimethylsiloxane, 2-5 parts of trimesicaldehyde, 80-100 parts of hexadecyl trimethylsiloxane, 50-70 parts of methyl trimethoxysiloxane, and 3300-3400 parts of solvent;
[0014] The solvent is a mixed solution of tetrahydrofuran and ethanol in a volume ratio of 0.9-1.1:0.9-1.1.
[0015] The second aspect of the present invention provides a method for preparing the above-mentioned lignin nanobottle-based photothermal superhydrophobic deicing coating composition, comprising:
[0016] Add the ammonia-propyl-terminated polydimethylsiloxane and mellitic aldehyde into a solvent and stir to obtain the first slurry;
[0017] Add the aged modified lignin nanobottles, cetyltrimethylsiloxane and methyltrimethoxysilane into a solvent to obtain the second slurry;
[0018] Mix the first slurry and the second slurry to obtain the lignin nanobottle-based photothermal superhydrophobic de-icing coating.
[0019] In some embodiments of the present invention, the preparation method of the aged modified lignin nanobottles is: obtained by heating and aging the lignin nanobottles.
[0020] Preferably, obtained by aging the lignin nanobottle solution at 80 - 200 °C for 2 - 20 h and then drying.
[0021] More preferably, the drying is freeze-drying.
[0022] In some embodiments of the present invention, the solvent of the first slurry includes any one of tetrahydrofuran, ethanol and acetone, preferably tetrahydrofuran.
[0023] In some embodiments of the present invention, the solvent of the second slurry includes any one of tetrahydrofuran, ethanol and acetone, preferably ethanol.
[0024] In some embodiments of the present invention, the first slurry and the second slurry are mixed in equal volume.
[0025] In the third aspect of the present invention, there is provided a lignin nanobottle-based photothermal superhydrophobic de-icing coating, which is obtained by spraying the above-mentioned lignin nanobottle-based photothermal superhydrophobic de-icing coating composition or the lignin nanobottle-based photothermal superhydrophobic de-icing coating composition prepared by the above-mentioned preparation method onto the surface of an aluminum alloy substrate and then curing.
[0026] In the fourth aspect of the present invention, there is provided an application of the above-mentioned lignin nanobottle-based photothermal superhydrophobic de-icing coating in de-icing.
[0027] The beneficial effects of the present invention are:
[0028] The present invention provides a lignin nanobottle-based photothermal superhydrophobic deicing coating composition, including cured and modified lignin nanobottles, aminopropyl-terminated polydimethylsiloxane, benzene-1,3,5-tricarbaldehyde, etc. The stability and photothermal performance of the lignin nanobottles are enhanced through curing and modification. The aminopropyl-terminated polydimethylsiloxane and benzene-1,3,5-tricarbaldehyde undergo a Schiff base reaction to form an imine bond-crosslinked hydrophobic supramolecular polymer, ensuring that the coating has excellent self-healing properties and enhanced coating stability. The cooperation of various components greatly improves the hydrophobicity, weather resistance, and deicing performance of the coating, and extends the service life of the coating. Moreover, the lignin nanobottle-based photothermal superhydrophobic deicing coating provided by the present invention does not rely on fluorides and is green, environmentally friendly, and pollution-free.
[0029] The preparation process of the lignin nanobottle-based photothermal superhydrophobic deicing coating composition provided by the present invention is simple, green, and environmentally friendly, and is suitable for large-scale production.
[0030] The superhydrophobic coating prepared by spraying the lignin nanobottle-based photothermal superhydrophobic deicing coating composition on the surface of an aluminum alloy substrate has excellent self-healing properties and weather resistance, expanding the scope of practical applications. It has very excellent deicing performance and can extend the icing time from 50 s to 1683 s in an environment of -20°C. At the same time, it only takes 12 s for the ice to slide off to achieve the purpose of deicing. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The specification drawings forming a part of the present invention are used to provide a further understanding of the present invention. The schematic embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention.
[0032] Figure 1 For the hydrophobic angle and contact angle of the wear test of the lignin nanobottle-based photothermal superhydrophobic deicing coating obtained in Example 4 of the present invention;
[0033] Figure 2 For the passive deicing process of the lignin nanobottle-based photothermal superhydrophobic deicing coating obtained in Example 4 of the present invention;
[0034] Figure 3 For the active deicing process of the lignin nanobottle-based photothermal superhydrophobic deicing coating obtained in Example 4 of the present invention;
[0035] Figure 4 For the contact angle diagram of the lignin nanobottle-based photothermal superhydrophobic deicing coating obtained in Example 4 of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0036] Aiming at the poor weather resistance, hydrophobicity, photothermal performance, and self-healing performance of the superhydrophobic coatings in the prior art, which seriously affect the service life and deicing effect of the hydrophobic deicing coatings, the present invention provides a lignin nanobottle-based photothermal superhydrophobic deicing coating and its preparation method and application.
[0037] In the first typical embodiment of the present invention, a lignin nanobottle-based photothermal superhydrophobic deicing coating composition is provided. By mass, it includes: 1-20 parts of aged and modified lignin nanobottles, 1-10 parts of aminopropyl-terminated polydimethylsiloxane, 1-10 parts of mesitylene tricarbaldehyde, 10-100 parts of cetyltrimethylsiloxane, 10-70 parts of methyltrimethoxysilane, and 3000-3500 parts of solvent.
[0038] The present invention uses aged and modified lignin nanobottles to prepare a superhydrophobic deicing coating. Under high-temperature stimulation, lignin molecules will undergo irreversible condensation, enhancing the stability and photothermal properties of lignin nanobottles and improving the weather resistance and deicing performance of the coating. Under the action of temperature, β-O-4 ether bonds and C-C bonds break, as well as hydroxyl groups and -OCH3 lignin molecular groups break, resulting in the formation of more free radicals in the lignin nanobottles. In addition, a large number of adjacent intramolecular and intermolecular free radicals simultaneously generate chemical crosslinks through α-5, β-5, β-β bonds, etc., enhancing the stability and photothermal properties of lignin nanobottles.
[0039] The present invention adds aminopropyl-terminated polydimethylsiloxane and mesitylene tricarbaldehyde to the lignin nanobottle-based photothermal superhydrophobic deicing coating composition. These two components form an imine bond-crosslinked hydrophobic supramolecular polymer through a Schiff base reaction. The imine bond is a dynamic covalent bond with high bond energy and dynamic reversibility, ensuring that the coating has excellent self-healing and mechanical robustness.
[0040] Through the cooperation of various components, the present invention synergistically improves various properties of the coating, enabling the coating to have excellent weather resistance, self-repair performance, and deicing performance, and extending the service life of the superhydrophobic deicing material.
[0041] In some embodiments of this embodiment, the aged and modified lignin nanobottles are obtained by heating and aging lignin nanobottles. Preferably, the lignin nanobottle solution is aged at 80-200 °C for 2-20 h and then dried to obtain the aged and modified lignin nanobottles. Temperature affects the degree of aging and modification of lignin nanobottles. If the temperature is too low, the degree of covalent crosslinking between lignin molecules is low, resulting in low stability of lignin nanobottles; if the temperature is too high, the structure of lignin nanobottles will be damaged, reducing its stability. Within the above temperature range, the obtained aged and modified lignin nanobottles have good stability and photothermal properties.
[0042] In some embodiments of this embodiment, aging is carried out at 80-180 °C for 2-12 h. Within the above range, as the temperature and time increase, the micro-nano structure, photothermal properties, stability, and hydrophobicity of the obtained aged and modified lignin nanobottles are all enhanced.
[0043] In some examples of this embodiment, the lignin nanobottle-based photothermal superhydrophobic deicing coating composition includes, by mass, 5-15 parts of mature modified lignin nanobottle, 2-8 parts of aminopropyl-terminated polydimethylsiloxane, 2-8 parts of trimesic acid, 30-100 parts of hexadecyl trimethylsiloxane, 30-70 parts of methyl trimethoxysiloxane, and 3300-3400 parts of solvent. Specifically, the mature modified lignin nanobottle can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts, etc., the propyl-terminated polydimethylsiloxane can be 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts or 8 parts, etc., the trimesic acid can be 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts or 8 parts, etc., the hexadecyl trimethylsiloxane can be 30 parts, 40 parts , 50 parts, 60 parts, 70 parts, 80 parts, 90 parts or 100 parts and the like, the methyl trimethoxy siloxane can be 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts or 70 parts and the like, and the solvent can be 3300 parts, 3310 parts, 3320 parts, 3330 parts, 3340 parts, 3350 parts, 3360 parts, 3370 parts, 3380 parts, 3390 parts or 3400 parts and the like.
[0044] In some examples of this embodiment, the lignin nanobottle-based photothermal superhydrophobic deicing coating composition includes, by weight: 10-15 parts of matured modified lignin nanobottle, 5-8 parts of aminopropyl-terminated polydimethylsiloxane, 2-5 parts of trimesicaldehyde, 80-100 parts of hexadecyl trimethylsiloxane, 50-70 parts of methyl trimethoxysiloxane, and 3300-3400 parts of solvent;
[0045] The solvent is a mixed solution of tetrahydrofuran and ethanol in a volume ratio of 0.9-1.1:0.9-1.1.
[0046] The coating prepared by the lignin nanobottle-based photothermal superhydrophobic deicing coating composition obtained by the formula has excellent weather resistance, self-repairing performance and deicing performance.
[0047] A second typical embodiment of the present invention provides a method for preparing the above-mentioned lignin nanobottle-based photothermal superhydrophobic deicing coating composition, comprising:
[0048] Adding aminopropyl-terminated polydimethylsiloxane and trimesic acid aldehyde into a solvent and stirring to obtain a first slurry;
[0049] adding the ripened modified lignin nanobottle, hexadecyl trimethylsiloxane and methyl trimethoxysiloxane into a solvent to obtain a second slurry;
[0050] Mix the first slurry and the second slurry to obtain a lignin nanobottle-based photothermal superhydrophobic deicing coating.
[0051] In some embodiments of this embodiment, the method for preparing the cured modified lignin nanobottle is: obtained by heating and curing the lignin nanobottle.
[0052] In some embodiments of this embodiment, the lignin nanobottle solution is cured at 80 - 200 °C for 2 - 20 h and then dried.
[0053] In some embodiments of this embodiment, the drying is freeze-drying.
[0054] In some embodiments of this embodiment, the solvent of the first slurry includes any one of tetrahydrofuran, ethanol, and acetone, preferably tetrahydrofuran.
[0055] In some embodiments of this embodiment, the stirring is as follows: the stirring speed is 300 - 800 rpm, more preferably 400 - 600 rpm; the stirring time is 1 - 5 h, more preferably 1 - 2 h. Appropriate stirring speed and stirring time are beneficial for the full reaction of aminopropyl-terminated polydimethylsiloxane and mellitic trialdehyde to generate more imine bonds to improve the self-healing performance of the coating. At the same time, appropriate stirring speed and stirring time are beneficial for the complete reaction of lignin nanobottles with cetyltrimethylsiloxane and methyltrimethoxysilane, resulting in improved hydrophobicity of the cured modified lignin nanobottles.
[0056] In some embodiments of this embodiment, the solvent of the second slurry includes any one of tetrahydrofuran, ethanol, and acetone, preferably ethanol.
[0057] In some embodiments of this embodiment, the first slurry and the second slurry are mixed in equal volumes.
[0058] In the third typical embodiment of the present invention, a lignin nanobottle-based photothermal superhydrophobic deicing coating is provided, which is obtained by spraying the above-mentioned lignin nanobottle-based photothermal superhydrophobic deicing coating composition or the lignin nanobottle-based photothermal superhydrophobic deicing coating composition prepared by the above-mentioned preparation method onto the surface of an aluminum alloy substrate and then curing.
[0059] In some embodiments of this embodiment, the curing is heat curing, the temperature is 60 - 110 °C, preferably 80 - 100 °C; the heating time is 0.5 - 6 h, preferably 3 - 5 h.
[0060] The lignin nanobottle-based photothermal superhydrophobic deicing coating provided by the present invention has self-healing property, strong weather resistance, photothermal performance, and a green and fluorine-free preparation process. In actual use, it has a high deicing effect, a long service life, and higher safety.
[0061] The fourth typical embodiment of the present invention provides an application of the above-mentioned lignin nanobottle-based photothermal superhydrophobic deicing coating in deicing.
[0062] It can be understood that the deicing is to coat the lignin nanobottle-based photothermal superhydrophobic deicing coating on the surface of the aluminum alloy substrate to be protected, so as to reduce the adverse impact that the icing phenomenon may cause on the normal operation of the aluminum alloy substrate or equipment. For example, the lignin nanobottle-based photothermal superhydrophobic deicing coating can be covered on the transmission line to achieve active deicing and passive deicing, and ensure the safe operation of the power grid.
[0063] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with specific embodiments.
[0064] The raw materials used in the following examples and comparative examples are all conventional commercially available products and can be obtained by purchase. Among them, the lignin nanobottles are prepared by the method of Example 1 in the patent "CN118530473A A highly homogeneous lignin nanobottle and its preparation method and application".
[0065] Example 1
[0066] A preparation method of a lignin nanobottle-based photothermal superhydrophobic deicing coating includes the following steps:
[0067] (1) Place 75 mL of 1 mg / mL lignin nanobottle solution in a 100 mL high-pressure reactor and cure and modify it at 100 °C for 6 h. After freeze-drying the cured and modified lignin nanobottle solution, obtain the cured and modified lignin nanobottle powder.
[0068] (2) Add 76.8 mg of aminopropyl-terminated polydimethylsiloxane and 33.2 mg of benzene-1,3,5-tricarbaldehyde to 20 mL of tetrahydrofuran and stir to react to obtain solution A.
[0069] (3) Add 15 mg of the cured and modified lignin nanobottles, 150 μL of cetyltrimethylsiloxane and 100 μL of methyltrimethylsiloxane to 3 mL of ethanol, stir and mix evenly to obtain solution B.
[0070] (4) Mix 2 mL of solution A and 2 mL of solution B, stir to obtain a superhydrophobic coating, the stirring speed is 400 rpm, and the stirring time is 1 h.
[0071] (5) Pour the superhydrophobic coating into the spray gun according to the spraying amount of 1 mL / cm 2 , and spray the coating on the surface of the aluminum alloy substrate under the conditions of 0.1 MPa and a spray test sample distance of 15 cm. Finally, dry the solvent at 105 °C to obtain the lignin nanobottle-based photothermal superhydrophobic deicing coating.
[0072] Example 2
[0073] A preparation method of a lignin nanobottle-based photothermal superhydrophobic deicing coating, comprising the following steps:
[0074] (1) Place 75 mL of 1 mg / mL lignin nanobottle solution in a 100 mL autoclave and cure and modify it at 180 °C for 12 h. After freeze-drying the cured and modified lignin nanobottle solution, obtain the cured and modified lignin nanobottle powder.
[0075] (2) Add 76.8 mg of aminopropyl-terminated polydimethylsiloxane and 33.2 mg of mellitic aldehyde to 20 mL of tetrahydrofuran and stir to react to obtain solution A.
[0076] (3) Add 9 mg of cured and modified lignin nanobottles, 150 μL of cetyltrimethylsiloxane, and 100 μL of methyltrimethylsiloxane to 3 mL of ethanol, stir and mix evenly to obtain solution B.
[0077] (4) Mix 2 mL of solution A and 2 mL of solution B, stir to obtain the superhydrophobic coating, the stirring speed is 400 rpm, and the stirring time is 1 h.
[0078] (5) Pour the superhydrophobic coating into a spray gun according to the spraying amount of 1 mL / cm 2 , under the conditions of 0.1 MPa and a spraying distance of 15 cm from the test sample, spray the coating on the surface of the aluminum alloy substrate, and finally volatilize the solvent at 105 °C to obtain the lignin nanobottle-based photothermal superhydrophobic deicing coating.
[0079] Example 3
[0080] A preparation method of a lignin nanobottle-based photothermal superhydrophobic deicing coating, comprising the following steps:
[0081] (1) Place 75 mL of 1 mg / mL lignin nanobottle solution in a 100 mL autoclave and cure and modify it at 180 °C for 6 h. After freeze-drying the cured and modified lignin nanobottle solution, obtain the cured and modified lignin nanobottle powder.
[0082] (2) Add 33.2 mg of aminopropyl-terminated polydimethylsiloxane and 76.8 mg of mellitic aldehyde to 20 mL of tetrahydrofuran and stir to react to obtain solution A.
[0083] (3) Add 21 mg of cured and modified lignin nanobottles, 50 μL of cetyltrimethylsiloxane, and 50 μL of methyltrimethylsiloxane to 3 mL of ethanol, stir and mix evenly to obtain solution B.
[0084] (4) Mix 2 mL of solution A and 2 mL of solution B, and stir to prepare a superhydrophobic coating at a stirring speed of 400 rpm for 1 h.
[0085] (5) Pour the superhydrophobic coating into a spray gun at a spraying amount of 1 mL / cm 2 , and spray the coating on the surface of an aluminum alloy substrate under the conditions of 0.1 MPa and a spray test sample distance of 15 cm. Finally, dry the solvent at 105 °C to obtain a lignin nanobottle-based photothermal superhydrophobic deicing coating.
[0086] Example 4
[0087] A preparation method of a lignin nanobottle-based photothermal superhydrophobic deicing coating includes the following steps:
[0088] (1) Place 75 mL of 1 mg / mL lignin nanobottle solution in a 100 mL high-pressure reactor and cure and modify it at 180 °C for 12 h. After freeze-drying the cured and modified lignin nanobottle solution, obtain cured and modified lignin nanobottle powder.
[0089] (2) Add 76.8 mg of aminopropyl-terminated polydimethylsiloxane and 33.2 mg of benzene-1,3,5-tricarbaldehyde to 20 mL of tetrahydrofuran and stir to react to prepare solution A.
[0090] (3) Add 21 mg of cured and modified lignin nanobottles, 150 μL of cetyltrimethylsiloxane, and 100 μL of methyltrimethylsiloxane to 3 mL of ethanol, and stir and mix evenly to prepare solution B.
[0091] (4) Mix 2 mL of solution A and 2 mL of solution B, and stir to prepare a superhydrophobic coating at a stirring speed of 400 rpm for 1 h.
[0092] (5) Pour the superhydrophobic coating into a spray gun at a spraying amount of 1 mL / cm 2 , and spray the coating on the surface of an aluminum alloy substrate under the conditions of 0.1 MPa and a spray test sample distance of 15 cm. Finally, dry the solvent at 105 °C to obtain a lignin nanobottle-based photothermal superhydrophobic deicing coating.
[0093] Example 5
[0094] A preparation method of a lignin nanobottle-based photothermal superhydrophobic deicing coating includes the following steps:
[0095] (1) Place 75 mL of 1 mg / mL lignin nanobottle solution in a 100 mL high-pressure reactor and cure and modify it at 180 °C for 12 h. After freeze-drying the cured and modified lignin nanobottle solution, obtain cured and modified lignin nanobottle powder.
[0096] (2) Add 76.8 mg of aminopropyl-terminated polydimethylsiloxane and 33.2 mg of mellitic aldehyde to 20 mL of tetrahydrofuran, and stir to react to obtain solution A.
[0097] (3) Add 21 mg of cured and modified lignin nanobottles, 150 μL of cetyltrimethylsiloxane, and 100 μL of methyltrimethylsiloxane to 3 mL of ethanol, and stir and mix evenly to obtain solution B.
[0098] (4) Mix 2 mL of solution A and 2 mL of solution B, and stir to obtain a superhydrophobic coating. The stirring speed is 400 rpm, and the stirring time is 1 h.
[0099] (5) Pour the superhydrophobic coating into a spray gun at a spraying amount of 1 mL / cm 2 , and spray the coating on the surface of the aluminum alloy substrate under the conditions of 0.1 MPa and a spray test sample distance of 15 cm. Finally, dry the solvent at 80 °C to obtain a lignin nanobottle-based photothermal superhydrophobic deicing coating.
[0100] Example 6
[0101] A preparation method of a lignin nanobottle-based photothermal superhydrophobic deicing coating includes the following steps:
[0102] (1) Place 75 mL of 1 mg / mL lignin nanobottle solution in a 100 mL high-pressure reactor and cure and modify it at 180 °C for 12 h. After freeze-drying the cured and modified lignin nanobottle solution, obtain cured and modified lignin nanobottle powder.
[0103] (2) Add 76.8 mg of aminopropyl-terminated polydimethylsiloxane and 33.2 mg of mellitic aldehyde to 20 mL of tetrahydrofuran, and stir to react to obtain solution A.
[0104] (3) Add 9 mg of cured and modified lignin nanobottles, 150 μL of cetyltrimethylsiloxane, and 100 μL of methyltrimethylsiloxane to 3 mL of ethanol, and stir and mix evenly to obtain solution B.
[0105] (4) Mix 2 mL of solution A and 2 mL of solution B, and stir to obtain a superhydrophobic coating. The stirring speed is 400 rpm, and the stirring time is 1 h.
[0106] (5) Pour the superhydrophobic coating into a spray gun at a spraying amount of 0.5 mL / cm 2 , and spray the coating on the surface of the aluminum alloy substrate under the conditions of 0.1 MPa and a spray test sample distance of 15 cm. Finally, dry the solvent at 105 °C to obtain a lignin nanobottle-based photothermal superhydrophobic deicing coating.
[0107] Example 7
[0108] A preparation method of a lignin nanobottle-based photothermal superhydrophobic deicing coating, comprising the following steps:
[0109] (1) Place 75 mL of 1 mg / mL lignin nanobottle solution in a 100 mL autoclave and cure and modify it at 180 °C for 12 h. After freeze-drying the cured and modified lignin nanobottle solution, obtain the cured and modified lignin nanobottle powder.
[0110] (2) Add 33.2 mg of aminopropyl-terminated polydimethylsiloxane and 78.4 mg of benzene-1,3,5-tricarbaldehyde to 20 mL of tetrahydrofuran and stir to react to obtain solution A.
[0111] (3) Add 9 mg of cured and modified lignin nanobottles, 50 μL of cetyltrimethylsiloxane, and 50 μL of methyltrimethylsiloxane to 3 mL of ethanol, stir and mix evenly to obtain solution B.
[0112] (4) Mix 1 mL of solution A and 2 mL of solution B, stir to obtain the superhydrophobic coating, the stirring speed is 400 rpm, and the stirring time is 1 h.
[0113] (5) Pour the superhydrophobic coating into a spray gun according to a spraying amount of 1 mL / cm 2 Under the conditions of 0.1 MPa and a spraying distance of 15 cm from the sample, spray the coating on the surface of the aluminum alloy substrate, and finally volatilize the solvent at 105 °C to obtain the deicing coating.
[0114] Comparative Example 1
[0115] A preparation method of a lignin nanobottle-based photothermal superhydrophobic deicing coating, comprising the following steps:
[0116] Compared with Example 4, the difference is that in this comparative example, step (1) will be deleted, and lignin nanobottles will be used to replace the cured and modified lignin nanobottles in step (4), and the remaining steps are the same as those in Example 4.
[0117] Comparative Example 2
[0118] A preparation method of a lignin nanobottle-based photothermal superhydrophobic deicing coating, comprising the following steps:
[0119] Compared with Example 4, the difference is that in this comparative example, step (2) is modified to: add 110 mg of aminopropyl-terminated polydimethylsiloxane to 20 mL of tetrahydrofuran and stir to react to obtain solution A, and the remaining steps are the same as those in Example 4.
[0120] Comparative Example 3
[0121] A preparation method of a lignin nanobottle-based photothermal superhydrophobic deicing coating, comprising the following steps:
[0122] Compared with Example 4, the difference is that in this comparative example, step (2) is modified as follows: 110 mg of benzene-1,3,5-tricarboxaldehyde is added to 20 mL of tetrahydrofuran and stirred to react to obtain solution A, and the remaining steps are the same as those in Example 4.
[0123] Comparative Example 4
[0124] Classical preparation method of lignin superhydrophobic coating:
[0125] (1) Weigh 2 g of kraft lignin using an electronic balance and disperse it in 60 mL of deionized water. Stir at 300 r / min at room temperature for 5 min to obtain solution A. Pour solution A into a 250 mL three-necked flask and continue stirring. Nitrogen is introduced at a flow rate of 0.5 m 3 / h. Weigh 3.5 g of imidazole and add it to solution A, and stir for 1 h. Use a measuring cylinder to pour acetone into a beaker, and use a measuring cylinder to measure 2 mL of perfluorooctyltriethoxysilane (FOTS) and pour it into 36 mL of acetone solution. Seal the beaker with a sealing film and stir at 300 r / min for 1 h to obtain solution B. Use an acid burette to drop solution B into solution A, heat to 50 °C and stir for 24 h, then pour 300 mL of deionized water to precipitate the lignin. Let it stand for 30 min, pour solution A into a centrifuge tube, place it in a centrifuge to centrifuge and precipitate for 10 min, pour out the supernatant, put the precipitate into a vacuum drying oven, and dry it at 85 °C under vacuum for 12 h to obtain silane-modified lignin.
[0126] (2) Weigh 100 mg of silane-modified lignin and 100 mg of nano-silica using an electronic balance and blend them in 10 mL of acetone to obtain solution C. Use a pipette to transfer 0.16 mL of polydimethylsiloxane and 0.05 mL of epoxy resin, and discharge them into solution C. Stir at 500 r / min at room temperature for 15 min. Use a pipette to measure 0.016 mL of polydimethylsiloxane curing agent and 0.05 mL of diethylenetriamine and discharge them into solution C, and stir for 15 min to obtain a superhydrophobic coating.
[0127] (3) Pour the superhydrophobic coating into an airbrush according to a spraying amount of 0.0016 g / cm 2 . Adjust the airbrush nozzle diameter to 0.5 mm, keep a distance of 15 cm between the airbrush and the specimen, spray on the specimen surface, and then put it into a vacuum drying oven and cure it at 85 °C for 10 h to obtain a superhydrophobic coating.
[0128] Comparative Example 5
[0129] Aluminum alloy substrate without any surface treatment.
[0130] Experimental Example 1:
[0131] (1) Hydrophobicity
[0132] The surface hydrophobicity of Examples 1-7 and Comparative Examples 1-5 was tested using a contact angle measuring instrument OCA50. 3 μL of water droplets were dropped on the surface of the sample, and its water contact angle was measured. The measurement results are shown in Table 1.
[0133] Table 1 Contact angles and sliding angles of examples and comparative examples
[0134]
[0135]
[0136] Note: "-" indicates that this data was not measured. The sliding angle usually describes the wettability of superhydrophobic materials. The sliding angle of non-superhydrophobic materials is usually too large and thus has no measurement significance.
[0137] As can be seen from Table 1, the hydrophobic angle of Comparative Example 5 was improved to varying degrees by the coating. Among them, the contact angles of Examples 1-7 of the present invention and Comparative Examples 2, 3, and 4 were all > 150°, meeting the requirement of the superhydrophobic coating for the contact angle (water contact angle > 150°); the sliding angles were all < 10°, meeting the requirement of the superhydrophobic coating for the sliding angle (sliding angle < 10°). Among them, the sliding angles of Examples 3, 4, 5, 7 and Comparative Example 4 were all < 2°. In contrast, Comparative Example 1 did not achieve superhydrophobic properties, indicating that the hydrothermal curing modification provided by the present invention greatly improved the hydrophobicity of lignin nanobottles and facilitated the preparation of lignin superhydrophobic coatings. In addition, the traditional lignin coating (Comparative Example 4) also met the requirement for the contact angle (water contact angle > 150°).
[0138] (2) Weather resistance test
[0139] Ⅰ: Abrasion test: The coating sample prepared in Example 4 under the optimal reaction conditions with a size of 2 cm × 2 cm was placed face to face on 1000-grit sandpaper with a size of 23 cm × 28 cm. A 100 g weight was attached to the back of the sample using double-sided tape to apply pressure to the coating. The sample was laterally moved a distance of 20 cm at a speed of 0.08 m s -1 . After every 10 abrasions, the contact angle and sliding angle of the sample were measured.
[0140] It can be seen from Figure 1 that the coating made from Example 4 under the optimal reaction conditions showed remarkable stability under severe mechanical abrasion. After multiple abrasions, the surface still maintained its superhydrophobicity, and the contact angle and sliding angle did not change significantly. It was proved that the coating had excellent abrasion resistance.
[0141] II: Acid-base test: Place the coating samples prepared in the examples and comparative examples with a size of 2 cm × 2 cm in an aqueous solution of 0.1 M HCl (pH = 1) or 0.1 M NaOH (pH = 13) and soak for 120 minutes. Record the contact angle and sliding angle of the samples every 30 minutes.
[0142] Table 2 Alkaline resistance (contact angle (°)) of the coatings obtained in the examples and comparative examples
[0143]
[0144]
[0145] Table 3 Alkaline resistance (contact angle (°)) of the coatings obtained in the examples and comparative examples
[0146] NaOH / min 0 120 Example 3 165.0 161.7 Example 4 169.1 166 Example 5 167.8 163.5 Example 7 165.8 160.7 Comparative Example 1 132.3 123.5 Comparative Example 2 153.2 78.8 Comparative Example 3 152.5 80.1 Comparative Example 4 158 128 Comparative Example 5 75.8 76.9
[0147] It can be seen from Table 2 and Table 3 that the coatings made from the examples show significant stability under severe chemical corrosion, and the contact angle has not changed significantly and still meets the requirements of superhydrophobic coatings. After soaking in an aqueous solution of 0.1 M HCl (pH = 1) or 0.1 M NaOH (pH = 13) for 120 min, the contact angle has not changed significantly and still meets the requirements of superhydrophobic coatings. However, the contact angle of Comparative Example 1 has changed to a large extent, which indicates that the aging treatment adopted in the present invention effectively improves the stability of lignin nanobottles. Due to the lack of a stable structure generated by the reaction of trimellitic aldehyde and aminopropyl-terminated polydimethylsiloxane in Comparative Example 2 and Comparative Example 3, the surface coating structure redissolves in the solution after immersion, resulting in the destruction of the superhydrophobic structure and the loss of superhydrophobic properties. In addition, the traditional lignin-based superhydrophobic coating (Comparative Example 4) also loses its superhydrophobic properties in a harsh environment.
[0148] (3) Self-healing test
[0149] After severely damaging the coated surfaces of the samples prepared in Example 4 and Comparative Example 4 under the best reaction conditions by plasma etching. Then place the plasma-etched coating at room temperature for 2 h for self-healing, and monitor its contact angle and sliding angle.
[0150] Table 4 Self-healing properties of the sample coatings prepared in Example 4 and Comparative Example 4
[0151]
[0152] Note: "-" indicates that this data was not measured. The sliding angle usually describes the wettability of superhydrophobic materials. The sliding angle of non-superhydrophobic materials is usually too large and thus has no measurement significance.
[0153] As can be seen from Table 4, the coating made from Example 4 under the optimal reaction conditions has excellent self-healing properties due to the dynamic imine bonds in the coating. At room temperature, the contact angle and sliding angle after self-healing can still achieve excellent superhydrophobic properties. In contrast, in Comparative Example 4, no dynamic imine bonds were formed in the coating, so the superhydrophobic properties were not restored.
[0154] (4) Ice removal test
[0155] Photothermal passive ice removal test: Under the condition of -20 °C, the icing process of water droplets on the coated surface of the sample of Example 4 under the optimal conditions under 1 sunlight irradiation was recorded, that is, the process of water droplets changing from transparent to opaque.
[0156] Photothermal active ice removal test: On the contrary, under the condition of -20 °C, the melting process of ice droplets on the coated surface of the sample of Example 4 under the optimal conditions under 1 sunlight irradiation was recorded, that is, the process of ice droplets changing from opaque to transparent water droplets.
[0157] Table 5 Results of photothermal passive ice removal test and photothermal active ice removal test
[0158] Example / Comparative Example Freezing time / s Ice block sliding time / s Example 4 1683 12 Comparative Example 1 156 - Comparative Example 4 185 39 Comparative Example 5 50 -
[0159] As can be seen from Table 5, Figure 2 and Figure 3 the coating made from Example 4 under the optimal conditions exhibits excellent ice removal ability. Compared with Comparative Example 1, Comparative Example 4, and Comparative Example 5, Example 4 can extend the icing time to 1683 s, and the passive ice removal effect is significantly improved. In terms of the active ice removal effect, Example 4 only needs 12 s to make the ice block slide off to achieve the ice removal purpose. In Comparative Example 1 and Comparative Example 5, due to the lack of superhydrophobic properties, the water after thawing has strong adhesion to the surface and cannot slide off. Since the lignin in Comparative Example 4 has poor photothermal performance, it takes 39 s for the ice block to slide off. The coating stabilities of Comparative Example 2 and Comparative Example 3 are too poor, and it is not of practical application value to study their ice removal performances.
[0160] The above are only the preferred embodiments of the present invention and are not used to limit the present invention. For those skilled in the art, the present invention can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.
Claims
1. A lignin nanobottle-based photothermal superhydrophobic deicing coating composition, characterized in that, By mass parts, it includes: 1-20 parts of cured modified lignin nanobottles, 1-10 parts of aminopropyl-terminated polydimethylsiloxane, 1-10 parts of mellitic aldehyde, 10-100 parts of cetyltrimethylsiloxane, 10-70 parts of methyltrimethoxysilane, and 3000-3500 parts of solvent.
2. The lignin nanobottle-based photothermal superhydrophobic deicing coating composition according to claim 1, wherein The cured modified lignin nanobottles are obtained by heating and curing lignin nanobottles; Preferably, the lignin nanobottle solution is cured at 80-200 °C for 2-20 h and then dried to obtain the cured modified lignin nanobottles; Preferably, the solvent includes at least one of tetrahydrofuran, ethanol, and acetone.
3. The lignin nanobottle-based photothermal superhydrophobic deicing coating composition according to claim 1, characterized in that, By mass parts, it includes: 5-15 parts of cured modified lignin nanobottles, 2-8 parts of aminopropyl-terminated polydimethylsiloxane, 2-8 parts of mellitic aldehyde, 30-100 parts of cetyltrimethylsiloxane, 30-70 parts of methyltrimethoxysilane, and 3300-3400 parts of solvent.
4. The lignin nanobottle-based photothermal superhydrophobic ice-removing coating composition according to claim 1, wherein By mass parts, it includes: 10-15 parts of cured modified lignin nanobottles, 5-8 parts of aminopropyl-terminated polydimethylsiloxane, 2-5 parts of mellitic aldehyde, 80-100 parts of cetyltrimethylsiloxane, 50-70 parts of methyltrimethoxysilane, and 3300-3400 parts of solvent; The solvent is a mixed solution of tetrahydrofuran and ethanol with a volume ratio of 0.9-1.1:0.9-1.
1.
5. A method for preparing the lignin nanobottle-based photothermal superhydrophobic deicing coating composition according to any one of claims 1-4, characterized in that, It includes: Add aminopropyl-terminated polydimethylsiloxane and mellitic aldehyde into the solvent and stir to obtain the first slurry; Add the cured modified lignin nanobottles, cetyltrimethylsiloxane, and methyltrimethoxysilane into the solvent to obtain the second slurry; Mix the first slurry and the second slurry to obtain the lignin nanobottle-based photothermal superhydrophobic deicing coating composition.
6. The preparation method according to claim 5, characterized in that, The preparation method of the cured modified lignin nanobottles is: obtained by heating and curing lignin nanobottles; Preferably, the lignin nanobottle solution is cured at 80-200 °C for 2-20 h and then dried to obtain; More preferably, the drying is freeze-drying.
7. The preparation method according to claim 5, characterized in that, The solvent of the first slurry includes any one of tetrahydrofuran, ethanol, and acetone, preferably tetrahydrofuran; The solvent of the second slurry includes any one of tetrahydrofuran, ethanol, and acetone, preferably ethanol.
8. The preparation method according to claim 5, characterized in that, The first slurry and the second slurry are mixed in equal volume.
9. A lignin nanobottle-based photothermal superhydrophobic de-icing coating, characterized in that, Spray the lignin nanobottle-based photothermal superhydrophobic deicing coating composition described in any one of claims 1-4 or the lignin nanobottle-based photothermal superhydrophobic deicing coating composition prepared by the preparation method described in any one of claims 5-8 onto the surface of an aluminum alloy substrate and cure to obtain.
10. An application of the lignin nanobottle-based photothermal superhydrophobic deicing coating described in claim 9 in deicing.
Citation Information
Patent Citations
Lignin-based super-hydrophobic coating and preparation method thereof
CN112608683A
Anti-icing coating, and preparation method therefor and use thereof
WO2024187576A1
AU2020101038A4